Pelatihan Jurnalistik Tingkat Dasar pada UKM Jurnalistik Universitas Nahdlatul Ulama Surabaya - Adi Saputra, Alfian (Humanist Journal, 2023)
Knowledge related to journalism among students is relatively low. This can be known through the work produced by an agency which is only produced by a handful of individuals. Based on the results of interviews, the cause of the lack of development of journalistic products is students' lack of understanding regarding the concepts and procedures for producing a journalistic product. UNUSA journalism UKM held a basic level II journalism training event. This activity is an event held every year in order to accept new members of UNUSA journalism UKM. This activity is one of the efforts to develop the skills of teenagers in Indonesia in the world of journalism/writing. Implementation of the service will begin on January 20-22 2023. Implementation of the service starts with data collection, program planning, presentation of ideas, coordination with related parties, program implementation and program evaluation. The implementation of this journalism training trains students' creativity in the field of journalism. This training lasted for 3 days, went smoothly and provided quite satisfactory results. Training was carried out effectively. Training is divided into several sessions. Each session, participants will receive material related to journalistic knowledge such as journalist ethics, photo-taking techniques, videotaking techniques, editorial and copywriting techniques and techniques for digging up story material. All material is explained coherently by resource persons who are experts in their fields.